Mitochondrial DNA and TLR9 activation contribute to SARS-CoV-2-induced endothelial cell damage - Costa, Tiago J.; Potje, Simone R.; Fraga-Silva, Thais F.C.; da Silva-Neto, Júlio A.; Barros, Paula R.; Rodrigues, Daniel; Machado, Mirele R.; Martins, Ronaldo B.; Santos-Eichler, Rosangela A.; Benatti, Maira N.; de Sá, Keyla S.G.; Almado, Carlos Eduardo L.; et al. (Vascular pharmacology, 2022)
Mitochondria play a central role in the host response to viral infection and immunity, being key to antiviral signaling and exacerbating inflammatory processes. Mitochondria and Toll-like receptor (TLR) have been suggested as potential targets in SARS-CoV-2 infection. However, the involvement of TLR9 in SARS-Cov-2-induced endothelial dysfunction and potential contribution to cardiovascular complications in COVID-19 have not been demonstrated. This study determined whether infection of endothelial cells by SARS-CoV-2 affects mitochondrial function and induces mitochondrial DNA (mtDNA) release. We also questioned whether TLR9 signaling mediates the inflammatory responses induced by SARS-CoV-2 in endothelial cells. Human umbilical vein endothelial cells (HUVECs) were infected by SARS-CoV-2 and immunofluorescence was used to confirm the infection. Mitochondrial function was analyzed by specific probes and mtDNA levels by real-time polymerase chain reaction (RT-PCR). Inflammatory markers were measured by ELISA, protein expression by western blot, intracellular calcium (Ca2+) by FLUOR-4, and vascular reactivity with a myography. SARS-CoV-2 infected HUVECs, which express ACE2 and TMPRSS2 proteins, and promoted mitochondrial dysfunction, i.e. it increased mitochondria-derived superoxide anion, mitochondrial membrane potential, and mtDNA release, leading to activation of TLR9 and NF-kB, and release of cytokines. SARS-CoV-2 also decreased nitric oxide synthase (eNOS) expression and inhibited Ca2+ responses in endothelial cells. TLR9 blockade reduced SARS-CoV-2-induced IL-6 release and prevented decreased eNOS expression. mtDNA increased vascular reactivity to endothelin-1 (ET-1) in arteries from wild type, but not TLR9 knockout mice. These events were recapitulated in serum samples from COVID-19 patients, that exhibited increased levels of mtDNA compared to sex- and age-matched healthy subjects and patients with comorbidities. SARS-CoV-2 infection impairs mitochondrial function and activates TLR9 signaling in endothelial cells. TLR9 triggers inflammatory responses that lead to endothelial cell dysfunction, potentially contributing to the severity of symptoms in COVID-19. Targeting mitochondrial metabolic pathways may help to define novel therapeutic strategies for COVID-19. [Display omitted] •Serum of COVID-19 patients present high levels of mtDNA•SARS-CoV-2 infects endothelial cells, which express ACE2 and TMPRSS2 proteins•SARS-CoV-2 promotes mitochondrial dysfunction, mtDNA release, TLR9 activation, and cytokines release•mtDNA induces vascular dysfunction in wild-type, but not TLR9 KO mice•TLR9 antagonism reduces IL-6 production in endothelial cells infected by SARS-CoV-2